Management of calls and threats in digital economy of Russia - V. N. Makhalin; O. M. Makhalina (Управление)
Development of digital economy of Russia is influenced by regularly arising calls and threats. The sphere of their emergence extensive and difficult predicted. The reasons of their emergence are connected with prob-lems of development of digital economy. In article the calls and threats arising on the way of development of digital economy which can rather conditionally be united in two groups are considered: the first group - organi-zational, technical and technological and the second group - information security. Similar division of the arising calls and threats promotes definition and the choice of forms and methods of fight against each of them. In article development barriers which often are a subject of calls and threats are considered and generalized. The first barrier - unavailability of the enterprises and organizations to be engaged in development of production and representation of services with use of network technologies. The second barrier is the lack of the qualified IT experts. The third barrier - ensuring cyber security. The fourth - threat of mass unemployment owing to introduction and development of IT technologies. Further the threats and calls connected with overcoming the fourth barrier, concerning perspective changes of labor market, the increasing role and influence of robotics are in more detail considered. Besides, increase of changes upon completion of which, by different estimates, tech-nologies of the Industry 4.0 will lead about 610 000 jobs to reduction is noted begun in the industry, under the influence of technological shift, but during the same period can also about 960 000 new vacancies will appear. A number of risks which are born in itself by «digitalization» and which are connected with possible loss of national originality, culture and language are considered. In article measures which, as a result of their application will allow to operate the arising technological hazards are brought and recommended and to increase the general scientific and technological level. Management of the arising calls and threats is a component of management of development of digital economy, but there are some features connected with uncertainty of their emergence both on time and in the direction and in the place. But it doesn’t exclude a possibility of risk management and threats according to the scheme of manage-ment of development of digital economy of an object